Enhancing teachers' pedagogical competence through the development of innovative learning tools based on the TPACK approach - Wibowo Heru Prasetiyo; Beti Indah Sari (Universitas Ahmad Dahlan, 2026)
This community service aimed to enhance the pedagogical competence of Pancasila and Civic Education (PPKn) teachers through a TPACK-based (Technological, Pedagogical, and Content Knowledge) workshop on innovative lesson plan (Rencana Pelaksanaan Pembelajaran/RPP) development. Low pedagogical competence in lesson planning remains a persistent challenge for PPKn teachers, as evidenced by below-standard national assessment scores. The workshop engaged junior and senior high school PPKn teachers affiliated with the Indonesian Pancasila and Citizenship Education Professional Association (AP3KnI) of East Java and was delivered online through interactive methods comprising theoretical instruction, learning strategy demonstrations, and guided hands-on practice. Evaluation results confirmed the workshop's effectiveness: mean pedagogical competence scores increased from 6.14 to 11.57, yielding an N-Gain of 63% (classified as